Aliphatic polycarbonate modified poly(ethylene furandicarboxylate) materials with improved ductility, toughness and high CO2 barrier performance. (19th April 2022) - Xie, Hongzhou; Meng, Hongxu; Wu, Linbo; Li, Bo-Geng; Dubois, Philippe
Abstract: Poly(ethylene 2, 5-furandicarboxylate) (PEF) is a promising biobased polymer possessing high strength, rigidity and gas barrier performance, but its poor ductility and toughness may limit its practical applications. In order to obtain PEF materials with improved ductility and impact toughness as well as high strength, modulus and excellent gas barrier performance, PEF with relatively low molecular weight was modified with aliphatic polycarbonate (APC) diols by chain extension/coupling in this study. The resulting products were mixtures composed of randomly segmented copolymers, chain extended APC and chain extended PEF. The APC moiety was proved to be partially miscible with the PEF matrix, and therefore plasticized the PEF matrix and promoted its cold crystallization. In comparison with PEF, the modified PEFs possess significantly enhanced tensile ductility and impact toughness. Particularly, the modified PEF containing 15 wt% poly(hexamethylene carbonate) exhibits balanced mechanical properties and CO2 barrier 5 times to PET. Graphical abstract: Image 1 Highlights: PEF was modified with aliphatic polycarbonates via chain extension & coupling. The APCs plasticized PEF and promoted its cold crystallization due to partial PEF/APC miscibility. 15–30 wt% APCs greatly improved ductility and toughness while keeping relatively high strength and modulus. PEF-PHC15 exhibits balanced mechanical properties and CO2 barrier 5 times to PET.